Níveis de mercúrio, prolactina e interleucina 10 em mulheres em idade reprodutiva e puérperas dos municípios de Itaituba e Ananindeua, Pará - JESUS, Iracina Maura de (Universidade Federal do Pará, 2013)
The ability of interfering in the immunological and endocrine organic systems has been attributed to the mercury (Hg), besides the nervous and renal systems frequently affected by this toxicant agent. Women in fertile age or pregnant constitute a vulnerable group for those effects, in relation to themselves and their fetus. The mercury exposure was assessed as well as the prolactin (PRL) and interleukin-10 (IL-10) levels in 144 women (in the post-partum and about one year later) of Itaituba, area under environmental Hg impact and in women of the metropolitan area of Belém, most of all from Ananindeua, area without known Hg impact (156 puerperal women and 156 non-puerperal). Total Hg (Hg-t) analyses in whole blood were carried out by Atomic Absorption Spectrometry Cold Vapor. Serum analyses of PRL were made by Enzyme Immunoassay with final detection by fluorescence and IL-10 serum analyses were accomplished by Enzyme Immunoassay of Solid Phase. Demographic and epidemiological data were obtained through semi-structured questionnaire. Puerperal women of Itaituba presented average of Hg-t, PRL and IL-10 of 13.93 μg/l, 276.20 ng/ml and 39.54 pg/ml, respectively. Puerperal women of Ananindeua presented respective Hg-t, PRL and IL-10 averages of 3.76 μg/l, 337.70 ng/ml and 4.90 pg/ml. Non-puerperal women of Itaituba presented Hg-t mean of 12.68 μg/l, PRL mean of 30.75 ng/ml and IL-10 mean of 14.20 pg/ml. Mean of Hg-t, PRL and IL-10 in non-puerperal women from Ananindeua were of 2.73 μg/l, 17.07 ng/ml and 1.49 pg/ml, respectively. Levels of Hg-t, PRL and IL-10 were higher in Itaituba (p<0.0001), except in PRL levels of puerperal women, higher in Ananindeua. Similar Hg levels in women of Itaituba in two assessment (p=0.7056) and positive correlation suggest continuity of exposure (r=0.4736, p<0.0001). The main predictor variable of mercury levels was the fish consumption in the linear and logistic multiple regression models. Parity and IL-10 levels were positively associated with PRL in puerperal women of Itaituba while newborn weight and IL-10 levels presented positive association with PRL in puerperal women of Ananindeua. IL-10 was negatively associated with PRL in non-puerperal women from Itaituba (p=0.0270) and positive association in Ananindeua (p=0.0266). Levels of Hg-t showed negative association with PRL in puerperal women and positive association with working in garimpo (p=0.0173) (the last one was also important for non-puerperal women) in Itaituba, according logistic models. IL-10 was positively associated with recent morbidity in puerperal women of Itaituba (p=0.0210), negatively with ingestion of alcoholic beverages (p=0.0178) and positively with working in garimpo in non-puerperal women (p=0.0199). The chronic Hg exposure of women from Itaituba, difference among the Hg, PRL and IL-10 levels in exposed women compared with non exposed group and association with relevant epidemiological variables, suggest the possibility of Hg impacts in the women's immunoendocrine system in Itaituba, calling attention for the health surveillance of this population and the possible use of assessment biomarkers as PRL.